SPATIAL ANALYSIS OF LAND COVER CHANGES IN DEPOK CITY USING GEOGRAPHIC INFORMATION SYSTEMS - Atri Prautama Dewi; Dwi Ariyani; Lulu Shafwah; Nadhira Nur Komariah (Jurnal Infrastruktur, 2024)
Depok City is an area undergoing significant changes in land cover due to rapid urban development. Additionally, population growth is contributing to these land cover changes. These factors exert pressure on land use changes, with implications for land cover. Therefore, it is necessary to conduct a spatial analysis of land cover changes in Depok City. This research employs Geographic Information System (GIS) methods and spatial analysis to examine land cover changes in Depok from 2017 to 2022. The objectives of this study are to identify the land cover conditions in Depok from 2017 to 2022 and analyze the changes in land cover during this period. The data source used is Landsat 8 satellite imagery. These satellite images were interpreted to produce land cover maps for the years 2017 and 2022. Subsequently, these two maps were overlaid to assess changes in land use. The research results revealed seven land cover classes in 2017, with the largest in terms of area being Residential/Built-up Areas (12,383.43 hectares), Green Open Spaces (3,479.66 hectares), Dryland Agriculture (2,218.65 hectares), Services/Industry (885.41 hectares), Paddy Fields (414.59 hectares), Open Land (373.66 hectares), and Water Bodies (239.23 hectares). Spatial analysis indicated a decrease in land cover for Green Open Spaces (238.84 hectares), Dryland Agriculture (122.67 hectares), and Paddy Fields (31.89 hectares). Conversely, an increase in land cover was observed for Residential/Built-up Areas (266.01 hectares), Services/Industry (91.84 hectares), and Open Land (35.55 hectares).